Origins of SARS-CoV-2: Window is closing for key scientific studies - Koopmans, M.; Daszak, P.; Dedkov, V.G.; Dwyer, D.E.; Farag, E.; Fischer, T.K.; Hayman, D.T.S.; Leendertz, F.; Maeda, K.; Hung Nguyen-Viet; Watson, J. (Springer, 2021)
Our group was convened by the World Health Organization (WHO) in October 2020. We have been the designated independent international members of a joint WHO–China team tasked with understanding the origins of SARS-CoV-2. Our report was published this March. It was meant to be the first step in a process that has stalled. Here we summarize the scientific process so far, and call for action to fast-track the follow-up scientific work required to identify how COVID-19 emerged, which we set out in this article.